Predictive Analytics On Academic Performance In Higher Education Institution During Covid-19 Using Regression Model - Muhammad Farezuan Zulfikri; Shazlyn Milleana Shaharudin; Noor Azrin Abdul Rajak; Muhammad Safwan Ibrahim (North Atlantic University Union NAUN, 2024)
Indexed by SCOPUS/ERA